Prenatal diagnosis of cephalothoracopagus janiceps: Sonographic-pathologic correlation - Luewan S. (2014)
Conjoined twins are identical twins whose bodies are joined in utero and are extremely rare complications of monochorionic twinning. They occur with incidence rates that range from 1 per 50,000 to 1 per 100,000 births; however, the incidence of the cephalothoracopagus variety is 1 per 58 conjoined twins.1 The precise etiology of conjoined twinning is unknown, but the most widely accepted theory is that incomplete division of a monozygotic embryo occurs approximately 13 to 15 days after ovulation. Conjoined twins are classified according to site of union. The most common location is the chest (thoracopagus). In this report, we describe a case of cephalothoracopagus janiceps with a fused head and thorax. This is the rarest form of conjoined twins with an incidence of 1 per every 3 million deliveries.2 The cephalopagus janiceps type of twins is characterized by 2 faces each looking in opposite directions on a single fused head. The face of each fetus is split in the midline with half turned outward, so that each observed face is made up of the right face of one fetus and the left face of the other. The term janiceps is derived from Janus, the 2-faced Roman god of gates and doorways.3 In the case of identical and symmetric faces caused by the orientations of the 2 notochordal axes that are perfectly ventroventral, they are called janiceps disymmetros.4 To our best knowledge, only 13 cases of janiceps twinning with prenatal diagnosis have been reported. A search of the PubMed for "janiceps" without any limitation revealed only 31 articles. Moreover, only 5 cases were prenatally described with 3-dimensional (3D) sonography 2,57 The objective of this report was to describe prenatal diagnosis and delineate the fused structures using both 2-dimensional (2D) and 3D sonography. © 2010 by the American Institute of Ultrasound in Medicine.